Punica granatum L. (Pomegranate) Extract: In Vivo Study of Antimicrobial Activity against Porphyromonas gingivalis in Galleria mellonella Model - Livia Aparecida Procópio Gomes; Lívia Mara Alves Figueiredo; Ana Luiza do Rosário Palma; Barbara Maria Corrêa Geraldo; Kelly Cristine Isler Castro; Luciana Ruano de Oliveira Fugisaki; Antônio Olavo Cardoso Jorge; Luciane Dias de Oliveira; Juliana Campos Junqueira (The Scientific World Journal)
Due to the increase of bacterial resistance, medicinal alternatives are being explored. Punica granatum L. is an effective herbal extract with broad spectrum of action and bactericidal, antifungal, anthelmintic potential and being able to modulate the immune response. The aim was to evaluate the antimicrobial activity of pomegranate glycolic extract (PGE) against the periodontal pathogen Porphyromonas gingivalis by using Galleria mellonella as in vivo model. Fifteen larvae were used per group. Injection of high concentration (200, 100, and 25 mg/mL) of PGE showed a toxic effect, leading them to death. A suspension of P. gingivalis (106 cells/mL) was inoculated in the left last proleg and PGE (12.5, 6.25, 3.1, and 2.5 mg/mL) were injected into the right proleg. The larvae were then kept at 37°C under the dark. Injection of PGE at any dose statistically improved larvae survival rates. The data were analysed (log-rank test, Mantel-Cox, P<0.05) and showed that all concentrations of PGE (12.5, 6.25, 3.1, and 2.5 mg/mL) presented higher larval survival rates, with significant statistical difference in relation to control group (P. gingivalis). In conclusion, the PGE had antimicrobial action against P. gingivalis in vivo model using G. mellonella.